2014
DOI: 10.1021/jp500011a
|View full text |Cite
|
Sign up to set email alerts
|

Energies of Electronic Transitions of Pentaerythritol Tetranitrate Molecules and Crystals

Abstract: Despite significant effort in research on energetic nitrocompounds coupled with a great interest in these materials for a range of technological and medical applications, the electronic structure of condensed energetic materials is barely studied. In this research aimed at a better understanding of the low energy absorption in the optical spectrum of nitro-compounds, the electronic structure and vertical electronic transitions of a gas-phase pentaerythritol tetranitrate (PETN) molecule and an ideal PETN crysta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
48
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(58 citation statements)
references
References 79 publications
10
48
0
Order By: Relevance
“…The optical absorption of PETN molecules and crystals were recently studied in great detail [23]. The UV absorption spectrum of PETN consists of three broad bands: a strong electronic transition at or below 193.5 nm (>6.41 eV) [37,38,39] and two weak transitions at 260 nm (4.77 eV) [37,38] and 290 nm (4.27 eV) [37].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The optical absorption of PETN molecules and crystals were recently studied in great detail [23]. The UV absorption spectrum of PETN consists of three broad bands: a strong electronic transition at or below 193.5 nm (>6.41 eV) [37,38,39] and two weak transitions at 260 nm (4.77 eV) [37,38] and 290 nm (4.27 eV) [37].…”
Section: Resultsmentioning
confidence: 99%
“…Our current research was inspired by an idea of achieving a highly controllable explosive decomposition chemistry initiated by photo-excitation with standard available lasers. In a series of recent experiments [18,19,20,21] and quantum-chemical simulations [22,23], it was fundamentally established that the decomposition of a high explosive material, PETN, can be reliably triggered by laser irradiation once PETN crystals are mixed with a small fraction of micron size metal oxide (e.g., MgO) powders. This demonstrated that there is a strong dependence of the initiation process on the presence of the oxide.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…4, which is different from that of RDX 0 . -HMX 0 , CL-20 0 and PETN 0 have a similar structures to RDX 0 [7,[9][10][11]35,37]. The detailed relaxation processes are given in supplementary information.…”
Section: Rdx Hmx Cl-20 and Petnmentioning
confidence: 99%
“…The photo-excitation process (process 1) is a widely studied process, and the excitation energy is clearly seen in the steady optical absorption spectra [34,36,37]. The nitro group exhibits special behavior owing to a large conjugated NO 2 π* orbital [10,15,16,18,19,30], which has been shown to be an energy pitfall for nitro explosives [15,16,[18][19][20].…”
Section: Experimental Evidence For the Relaxed Structurementioning
confidence: 99%